Sleep, major depressive disorder and Alzheimer’s disease: a Mendelian randomisation study - Huang,J; Zuber,V; Matthews,P; Tzoulaki,I; Elliott,P; Dehghan,A (Neurology, 2020)
ObjectiveTo explore the causal relationships between sleep, major depressive disorder (MDD), and Alzheimer’s disease (AD).MethodsWe conducted bi-directional two-sample Mendelian randomisation analyses. Genetic associations were obtained from the largest genome-wide association studies currently available in UK Biobank (N=446,118), the Psychiatric Genomics Consortium (N=18,759), and the International Genomics of Alzheimer’s Project (N=63,926). We used the inverse variance weighted Mendelian randomisation method to estimate causal effects, and weighted median and MR-Egger for sensitivity analyses to test for pleiotropic effects. ResultsWe found that higher risk of AD was significantly associated with being a “morning person” (odds ratio (OR)=1.01, P=0.001), shorter sleep duration (self-reported: β=-0.006, P=1.9×10-4; accelerometer-based: β=-0.015, P=6.9×10-5), less likely to report long sleep (β=-0.003, P=7.3×10-7), earlier timing of the least active 5 hours (β=-0.024, P=1.7×10-13), and a smaller number of sleep episodes (β=-0.025, P=5.7×10-14) after adjusting for multiple comparisons. We also found that higher risk of AD was associated with lower risk of insomnia (OR=0.99, P=7×10-13). However, we did not find evidence either that these abnormal sleep patterns were causally related to AD or for a significant causal relationship between MDD and risk of AD. ConclusionWe found that AD may causally influence sleep patterns. However, we did not find evidence supporting a causal role of disturbed sleep patterns for AD or evidence for a causal relationship between MDD and AD.